Conceptualizing confinement: Prisons and poverty in Sierra Leone. (February 2014) - Jefferson, Andrew M
This article develops an expansive notion of confinement as a lens through which to think about the lives of former prisoners, former fighters and slum dwellers in a post-conflict setting characterized by political volatility, exorbitant poverty and limited opportunities. The theoretical purpose of the article is to explore whether an expansive notion of confinement might help us make sense of the lives of people whose possibilities are limited materially, spatially and discursively. The intention – inspired by Loïc Wacquant, Zygmunt Bauman and archaeologist Eleanor Casella – is 'to move beyond the prison as the dominant optic for thinking about confinement'. The concept of confinement under development is illustrated with empirical examples culled from fieldwork in prisons and a poor urban neighbourhood in Freetown, Sierra Leone, West Africa. The orientation is towards confinement as site, practice and state of mind. The argument is that an expansive notion of confinement that attends to space, time, practices, meanings and states of mind is a useful way of thinking about the situated struggles of people living in prison and relative poverty.